Multi-criteria assessment of the benefits of a supply chain management training considering green issues - Tramarico, Claudemir Leif [UNESP]; Salomon, Valério Antonio Pamplona [UNESP]; Marins, Fernando Augusto Silva [UNESP] (Elsevier, 2017)
Green Supply Chain Management (GSCM) is an important issue for organizations that spend considerable amounts of investments on personnel training annually. Although these investments present positive effects, the manner to assess the effectiveness of the training is unclear. Training, whose characteristics are intangible, is sometimes difficult to be assessed. This research has carried out a multi-criteria training assessment for GSCM through the four top-level processes of Supply Chain Operations Reference Model (SCOR) i.e., Plan, Source, Make and Deliver. Analytic Hierarchy Process was applied in the training assessment. In the chemical industry where our study was performed, the SCOR top-level processes were considered criteria, whereas Individual and Organizational Benefits alternatives. The modeling considered pairwise judgments for criteria, and ratings or absolute measure for alternatives. The analysis revealed that training essentially contributes to the organization, resulting in 87% for Organizational Benefits, and 77% for Individual Benefits. Organizational Benefits focused on the use of the best practices in GSCM and on the common understanding of vocabulary and processes. In addition, Individual Benefits increased knowledge and skills in GSCM. This result, presented to managers of the company, was validated as consistent and feasible.
Keywords: Analytic Hierarchy Process; Green Supply Chain Management; SCOR; Supply Chain Management; Training